Role of BK human polyomavirus in cancer - Jorge Levican (Infectious Agents and Cancer, 2018)
Abstract Human polyomaviruses (HPyV), which are small DNA viruses classified into the polyomaviridae family, are widely distributed in human populations. Thirteen distinct HPyVs have been described to date. Some of these viruses have been found in human tumors, suggesting an etiological relationship with cancer. In particular, convincing evidence of an oncogenic role has emerged for a specific HPyV, the Merkel cell polyomavirus (MCPyV). This HPyV has been linked to rare skin cancer, Merkel cell carcinoma (MCC). This finding may be just the tip of the iceberg, as HPyV infections are ubiquitous in humans. Many authors have conjectured that additional associations between HPyV infections and neoplastic diseases will likely be discovered. In 2012, the International Agency for Research on Cancer (IARC) evaluated the carcinogenicity of the BK virus (BKPyV), reporting that BKPyV is “possibly carcinogenic to humans.” This review explores the BKPyV infection from a historical point of view, including biological aspects related to viral entry, tropism, epidemiology and mechanisms potentially involved in BKPyV-mediated human carcinogenesis. In order to clarify the role of this virus in human cancer, more epidemiological and basic research is strongly warranted.